2004
DOI: 10.1113/jphysiol.2003.060301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing and exercise training on endothelium‐dependent vasodilatation and structure of rat skeletal muscle arterioles

Abstract: Ageingreducesendothelium-dependentvasodilatationinhumansandanimals,andinhumans, exercise training reverses the ageing-associated reduction in endothelium-dependent vasodilatation. The purpose of this study was to determine the mechanism(s) by which 10-12 weeks of treadmill exercise enhances endothelium-dependent vasodilatation in muscles of differing fibre composition from young and old rats. Three-and 22-month-old male Fischer 344 rats were assigned to young sedentary, young exercise-trained, old sedentary, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
225
5
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(251 citation statements)
references
References 49 publications
20
225
5
1
Order By: Relevance
“…Studies on the regulation of capillarization in response to exercise and training have shown that acute exercise enhances the protein and mRNA levels of several angiogenic factors such as vascular endothelial growth factor (VEGF) (21,31), matrix metalloproteinase-2 (MMP-2) (6,15), and endothelial nitric oxide synthase (eNOS) (11,34). In addition, acute exercise has been shown to cause an increase in the muscle interstitial concentration of VEGF (18,21), which, at least in part, appears to reflect a release of VEGF from skeletal muscle cells as demonstrated in cultured muscle cells (22).…”
mentioning
confidence: 99%
“…Studies on the regulation of capillarization in response to exercise and training have shown that acute exercise enhances the protein and mRNA levels of several angiogenic factors such as vascular endothelial growth factor (VEGF) (21,31), matrix metalloproteinase-2 (MMP-2) (6,15), and endothelial nitric oxide synthase (eNOS) (11,34). In addition, acute exercise has been shown to cause an increase in the muscle interstitial concentration of VEGF (18,21), which, at least in part, appears to reflect a release of VEGF from skeletal muscle cells as demonstrated in cultured muscle cells (22).…”
mentioning
confidence: 99%
“…13 On the other hand, the forced wheel activity might alter the metabolic system by which the weight-gaining effect of chronic mismatches of circadian rhythms was counteracted. Previous studies have established that, with the activity intensity above certain levels, exercises -either voluntarily 20,21,30 or involuntarily [31][32][33] -increase food intake but reduce body weight gain when compared with sedentary controls, that is, exercises reduce feed efficiency. Furthermore, the serum cholesterol 34 and triglyceride 21,30,34 levels were lower and the organ weight of the lungs, hearts 33 and adrenal glands 21,33 was higher in rats that were exercised.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-trained rats (T) ran on the treadmill for 30 min, 5 days a week for 12 weeks (10). Each session included warm-up and cool-down periods (running 7 m/min, 0° incline).…”
Section: Exercise Training and Adaptation On The Rat Treadmillmentioning
confidence: 99%